BUSINESS STRATEGY INSIGHTS FROM HER HAVEN: A FEMALE-FOCUSED GUEST HOUSE IN JAKARTA - Wilson, Richard; Yulius, Kevin Gustian (Jurnal Bisnis Terapan, 2025)
The increasing demand for safe and exclusive accommodations among female travellers highlights a significant gap in the hospitality industry, particularly in urban centers like Jakarta. Her Haven Guest House aims to address this need by offering women-only lodging that prioritizes safety, comfort, and personalized experiences. This study analyses the marketing strategies required to establish Her Haven Guest House as a leading provider in this niche market. The research employs a mixed-methods approach, combining surveys, observations, and secondary data analysis to assess consumer preferences and market dynamics. Primary data was gathered through an online survey of 165 women aged 21-54 in the Greater Jakarta area, revealing a strong preference for women-only accommodations. The study applies the 8Ps marketing mix framework—Product, Price, Place, Promotion, People, Packaging, Programming, and Partnerships—to develop actionable strategies for the guest house. Additionally, a SWOT analysis identifies key strengths, weaknesses, opportunities, and threats, guiding strategic recommendations. The findings indicate that Her Haven Guest House can leverage its unique concept and strategic location to attract female travellers seeking security and exclusivity. The results highlight the importance of digital marketing, loyalty programs, and themed events in building brand awareness and customer loyalty. Furthermore, the study provides insights into managerial strategies to enhance service quality and policy recommendations for government support in promoting inclusive tourism. By addressing the specific needs of female travellers, Her Haven Guest House has the potential to contribute to the broader landscape of sustainable and inclusive hospitality.